2007
DOI: 10.1002/pmic.200601024
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better analysis of secreted proteins: the example of the myeloid cells secretome

Abstract: The analysis of secreted proteins represents a challenge for current proteomics techniques. Proteins are usually secreted at low concentrations in the culture media, which makes their recovery difficult. In addition, culture media are rich in salts and other compounds interfering with most proteomics techniques, which makes selective precipitation of proteins almost mandatory for a correct subsequent proteomics analysis. Last but not least, the non-secreted proteins liberated in the culture medium upon lysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(177 citation statements)
references
References 37 publications
0
172
1
4
Order By: Relevance
“…Protein precipitation using TCA was done as described by Chevallet et al (32). The cells in this experiment was incubated in RPMI 1640 media with 0.5% FBS.…”
Section: Trichloroacetic Acid Precipitationmentioning
confidence: 99%
“…Protein precipitation using TCA was done as described by Chevallet et al (32). The cells in this experiment was incubated in RPMI 1640 media with 0.5% FBS.…”
Section: Trichloroacetic Acid Precipitationmentioning
confidence: 99%
“…At day 11, the bone marrow cells are differentiated into DCs and ready for the various experiments. The resulting cells are essentially CD8-positive, and their cytokinic profile upon LPS activation is (IL-6/IL-12/TNF␣)/high, (IL-10/interferon ␥)/low (18). In some control experiments, dendritic cells were cultured without FLT3-L, leading to a much lower yield of cells.…”
Section: Cell Cultures For Proteomics Experimentsmentioning
confidence: 99%
“…In addition to the well known cytokine expression, which is even a test to check for dendritic cell activation with various stimuli (6,7,14), recent work has also shown that activated dendritic cells secrete many other proteins, such as proteases or complement proteins (18,28).…”
Section: Immature Dendritic Cells Secrete Extracellular Sensors-mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby only a ''truly'' secreted protein fraction was obtained, as opposed to the supernatant of culture cells which is usually composed of a mixture of secreted proteins, cytoplasmic proteins derived from dying cells and residual serum proteins. This issue was already addressed in an earlier study [85], where it was shown that the protein contamination in the DC culture media is linked to various classes of proteins, including cytoskeletal proteins and major metabolic enzymes. To overcome this problem, protein extracts from serum-depleted DC culture media were compared to extracts of total cell lysates in the media, creating a much more comparable 2-D pattern and allowing the identification of specific and truly secreted proteins by DCs.…”
Section: Studies On Fractionated Samples From Dcsmentioning
confidence: 92%